Reliability, validity, and factorial structure of the Turkish version of the Bradford Somatic Inventory (Turkish BSI-44) in a university student sample - KÖSE, SAMET (TAYLOR & FRANCIS LTD, 2017)
Objective: Mumford and colleagues developed the Bradford Somatic Inventory (BSI) that examines the somatic symptoms of anxiety and depression, which has transcultural applications. The objective of the current study was to establish the psychometric properties and factorial validity of the Turkish version of the BSI-44 in a healthy Turkish population and obtain normative data. Methods: The study was conducted at the Marmara University School of Medicine with a sample of 201 healthy students (18-30 years old). In order to estimate the test-retest reliability of the Turkish BSI, 53 participants from the original sample were asked to fill in the questionnaire one month after the initial testing. Socio-demographic data of the participants were collected and the Turkish BSI, Somatosensory Amplification Scale (SSAS), Whiteley Index (WI-7), and somatization subscale of the Symptom Check List (SCL-90-R) scales were administered. All statistical analysis were performed by using SPSS version 23 for Windows. Results: The mean age of the study participants was 22.9 +/- 1.95 years; 57.7% (n = 116) of participants were female; 42.3% (n = 85) were male. BSI scores were normally distributed. The scores of the BSI were categorized as high (> 40), middle (26-40), and low (0-25); no statistically significant differences were found between males and females. The Cronbach's alpha coefficient for the scale was 0.90 and the test-retest correlation coefficient was found to be 0.75. A positive and statistically significant correlation was found between the Turkish BSI and the WI (r = 0.38, p <.01), the SSAS (r = 0.48, p <.01) and the SCL-90-R (r = 0.79, p <.01) scales. A principal components analysis was performed on the BSI responses of the participants, which yielded 14 factors with an eigenvalue greater than one, representing 65.2% of the total variance. Conclusions: Our results suggested that the Turkish BSI was a valid and reliable tool with a robust factorial structure to use in clinical populations in Turkey.
Keywords: Somatization; Bradford Somatic Inventory; anxiety; depression; reliability; validity; factor structure; PRIMARY-CARE; SOMATIZATION; SYMPTOMS; IMMIGRANTS; DISORDERS; SCALE